Front Matter Jurnal ASET (Akuntansi Riset) Vol 9 No 2 July-December 2017 - Setiawan, Yana (Jurnal ASET (Akuntansi Riset), 2017)
FrontÂ Matter Jurnal ASET (Akuntansi Riset) Vol 9 No 2 July-December 2017